We bought a 3D printer for the library: this is our experience - Juárez-Urquijo, Fernando (Anuario ThinkEPI, 2021)
The maker movement is a social movement with a craft spirit through which digital fabrication methods have become accessible at a personal level. Public libraries are ideal for offering makerspaces that enable the collaborative use of tools and technologies to foster informal learning. Three-dimensional (3D) printing has been one of the keys to the expansion of the maker movement, and its presence in libraries, often identified as the "gateway" to the maker philosophy, is not unusual, albeit remaining more a desire than a reality. We recount herein our experience of purchasing and setting up a 3D printer to enable a reflection on makerspaces in a public library.